Adipose Tissue-Derived Stromal Cells Induce a Highly Trophic Environment While Reducing Maturation of Monocyte-Derived Dendritic Cells. (26th October 2020) - Juhl, Morten; Follin, Bjarke; Gad, Monika; Larsen, Jesper; Kastrup, Jens; Ekblond, Annette
Abstract : Allogeneic cell-based therapies using adipose tissue-derived stromal cells (ASCs) offer an off-the-shelf alternative to autologous therapy. An underlying assumption is that ASC can modulate the immune response of the recipient. However, in vitro models are required to explore and identify cell interactions and mechanisms of action, to ensure sufficient and sustained effects, and to document these. In this study, we shed light on the effect of ASC manufactured for clinical use on monocyte-derived dendritic cells and an inflammatory microenvironment. ASCs were isolated from healthy voluntary donors, expanded using a human platelet lysate in bioreactors, and cryopreserved as per clinical use. Monocyte-derived dendritic cells were generated by isolation of monocytes and differentiation with GM-CSF and IL-4. Dendritic cells were cocultured with different ratios of ASC and matured with LPS and IFN- γ . Dexamethasone was included as an immunosuppressive control. Dendritic cells were analyzed by flow cytometry for CD11c, CD40, CD80, CD83, CD86, PD-L1, and HLA-DR, and supernatants were analyzed for FGF2, HGF, IL-10, IL-12p70, LIF, MIF, PDGF, PlGF, and IDO. Reduced expression of maturation markers was observed on ASC-treated dendritic cells, while high levels of PD-L1 were maintained. Interestingly, the expression of CD83 was elevated. Escalating ratios of ASC did not affect the concentration of IL-10 considerably, whereas the presence of IL-12 was reduced in a dose-dependent manner. Besides offsetting the IL-12/IL-10 balance, the concentrations of IDO and MIF were elevated in cocultures. Concentrations of FGF2, HGF, LIF, and PIGF were high in ASC cocultures, whereas PDGF was depleted. In a robust coculture model, the addition of ASC to dendritic cells inhibited the dendritic maturation substantially, while inducing a less inflammatory and more tolerogenic milieu. Despite the exposure to dendritic cells and inflammatory stimuli, ASC resulted in supernatants with trophic factors relevant for regeneration. Thus, ASC can perform immunomodulation while providing a regenerative environment.